MEDIA NEEDS ANALYSIS OF SIMBOLA GENIALLY TO IMPROVE CIVIC LITERACY AND COLLABORATION OF GRADE II ELEMENTARY SCHOOL STUDENTS - Nur Bahja; Ari Metalin Ika Puspita; Raden Roro Nanik Setyowati (Jurnal Cakrawala Pendas, 2025)
This research aimed to develop Simbola Genially, an interactive learning media designed to enhance civic literacy and collaboration among second-grade elementary school students. Utilizing the ADDIE development model, the study focused on the analysis phase to determine the needs of students and teachers. Data were gathered through interviews and questionnaires involving 75 students. The findings demonstrated that Simbola Genially significantly aided 80% of students in understanding concepts, enhanced tolerance by 74.67%, responsibility by 72%, critical thinking by 77.33%, and love for the country by 86.67%. The study addressed the limitations of traditional teaching methods, which predominantly rely on government textbooks and one-way instructional approaches. Evaluations in these settings often focus on lower-order thinking skills, leaving higher-order skills and civic literacy underdeveloped. Simbola Genially integrates interactive visual and audio elements, incorporating Pancasila symbols to foster a more engaging and effective learning environment. The research concluded that there is a substantial need for Simbola Genially to enhance the teaching of Pancasila Education in elementary schools. This media supports the development of essential 21st-century skills, such as critical thinking and collaboration, by providing students with interactive and dynamic learning experiences. By leveraging technological advancements, Simbola Genially can create an immersive learning environment that not only improves students' civic literacy and collaborative skills but also makes learning more enjoyable and meaningful. The study’s results suggest that this media holds significant potential in improving the overall quality of civic education and fostering a deeper understanding of civic responsibilities among young learners.